Armenians in Georgia: Positive Examples of Coexistence and Development - Hovhannisyan, Haykaz; Kekelia, Vladimer; Vardanyan, Hratsin (Journal of Ecohumanism, 2025)
In the Matenadaran archive - Institute of Ancient Manuscripts in Yerevan (archive Alexander Yeritsyan- famous Armenian historian (1841-1902), one of member of the Caucasus Archaeographic Commission, as a result of which the 12-volume work «Acts of the Archaeographic Commission of the Caucasus (ACAC), there is a separate folder of documents No. 162, which are in Georgian. These documents have not been studied in either Armenian or Georgian historians. The documents illuminate and clarify various aspects of cooperation between the Armenians and Georgians. Hence, the current focus of the study on the history of the Armenian-Georgian cooperation is mainly devoted to the problems of the Armenian-Georgian internal life, economic and civil issues that were not politically motivated, which at the same time define and characterize the atmosphere of mutual respect and tolerance between the Armenian and Georgian population.